Monitoring indicators of vegetative and energy supply of activity in the process of human adaptation to long-term extreme living conditions - Zabrodina, Liudmyla; Pryvalova, Nataliya; Matkovskyi, Vasyl (Ukrainian Antarctic Journal, 2024)
The study was designed to trace winterers’ parameters of vegetative and energetic activity supply over time, arbitrary regulation of mental processes, and evaluation of sleep quality. It also aims to identify a complex of informative criteria for human adaptation to harsh living conditions. To this effect, we created an original model that allows to optimize diagnostics of people’s functional state and its dynamics given a variety of factors. We examined ten winterers (seven men and three women) whose mean age was 35.4 ± 2.0 years, and 18–28 records per participant were obtained for everyone. Three options for specific changes of adaptive and compensatory reactions in the participants of the long-term Antarctic expedition were observed. The first included pronounced vasomotor responses of the hypertonic type with preserved functions of the somnogenic mechanisms. In the second option, measured parameters remained almost always within the norm. For the third option, typical were vasomotor responses following the dystonic type, sleep disturbances of varying degrees, and unstable evaluations of health, activity, and mood, with a tendency to decrease. Under unfavorable changes in the vasomotor responses during the wintering season, the signs of maladaptive changes in the brain’s functional state were clearer. A relatively higher proportion of insufficiently adaptive productivity changes as a result of decreasing functional state was seen in the winterers with the first variety of adaptation dynamics. In the people with the second variety, a sufficient level of adaptation is often reached by a compensatory reaction type. As for the third variety, the subjects had the least representation of the stable reaction type and significant compensatory and exhaustive types. Thus, the results allow us to identify a complex of informative parameters that permits evaluating the quality and dynamics of human adaptation to long-term extreme life conditions. The data have to be considered to forecast work productivity in extreme conditions, study the quality and duration of adaptation, and plan measures to prevent the disruption of adaptive-compensatory mechanisms in the wintering team.